Teaching Science with the Papuan Ethnoscience Approach: Between Gaps and Opportunities for Developing Science Learning in the Future: A Literature Review - Jan Pieter; Putu Victoria M Risamasu (MASI Mandiri Edukasi, 2026)
Ethnoscience-based science education in Papua remains underdeveloped despite its potential to integrate indigenous knowledge into formal learning and improve students’ conceptual understanding. This systematic literature review aims to identify and analyze existing studies on ethnoscience-based science education in Papua. The study employed the PRISMA 2020 guidelines as the review protocol. The literature was systematically searched across DOAJ, Scopus, and national index databases. From 124 identified articles, only 8 met the predefined inclusion criteria and were selected for further analysis. The findings reveal that ethnoscience research in Papua remains limited, focusing predominantly on documenting indigenous science knowledge of the Malind tribe and on developing contextual teaching materials. The results also indicate that the ethnoscience approach is effective in improving students’ conceptual understanding while simultaneously supporting the preservation of local wisdom. However, significant research gaps remain, particularly in developing interactive learning media grounded in Papuan ethnoscience and in examining the long-term impact of such approaches on student learning outcomes.